A dialogue with Sen"s Theory of capabilities and its implications for our National Democratic Revolution - Vellem, Vuyani S. (HTS teologiese studies, 2016)
In ‘traditional’ liberation theological discourse, especially the Latin American strand, the concept of development, desarrollismo, that is developmentalism, has been severely critiqued. In recent times, the interpretation of development shifted to a number of models, one of which has been the view of development as freedom, associated with Amartya Sen’s ‘capabilities theory’. While the capabilities theory ostensibly comes closer to the goals of the liberation paradigm in general, this article seeks to critically explore in dialogue with this theory of capabilities assumptions and implications of the concept of development for our national democratic revolution. A number of service delivery strikes in our land, with many poor people expecting government to ‘deliver’ for them, might suggest among other things that the state does ‘development’ for people, hence the designation of the post-1994 South African state as a ‘developmental state’. This article argues that, at foundational level, development understood as liberation could help alter the assumptions that held the national democratic revolution back.